Personnel Policy Court of Justice of the Kazan during the First World War (1914-1917) - Rail Rashitovich Shaydullin (Управленческое консультирование)
The article discusses the features of the personnel policy of the Kazan Trial Chamber during the First World War. The main problems identified in the article - the question of employment evacuated ranks judiciary. In the district of Kazan Trial Chamber was а lot of refugees - members and employees of the judicial system, find themselves without а job. In some regions, there was а shortage of personnel in the other - the refugees themselves did not want to pursue legal action. The author shows the situation in Kazan, Sarapul, Vyatka, Yekaterinburg, Simbirsk, Ufa, Perm district courts, members of the judicial district of Kazan Trial Chamber.